2021
DOI: 10.1186/s13014-021-01924-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of inter-observer differences in the delineation of the target in spinal metastases SBRT using an automatic contouring dedicated system

Abstract: Background Approximately one third of cancer patients will develop spinal metastases, that can be associated with back pain, neurological symptoms and deterioration in performance status. Stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT) have been offered in clinical practice mainly for the management of oligometastatic and oligoprogressive patients, allowing the prescription of high total dose delivered in one or few sessions to small target volumes, minimizing the dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For a spine SBRT approach, correct definition of the treatment volume becomes even more important due to the nature of this treatment with high dose delivery per fraction and the proximity of critical OARs such as the spinal cord. Many studies have already demonstrated that inter-observer variability can be reduced by using the auto-segmentation tool ( 18 ). Our study also supports the findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a spine SBRT approach, correct definition of the treatment volume becomes even more important due to the nature of this treatment with high dose delivery per fraction and the proximity of critical OARs such as the spinal cord. Many studies have already demonstrated that inter-observer variability can be reduced by using the auto-segmentation tool ( 18 ). Our study also supports the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the autosegmentation tool Elements SmartBrush Spine (ESS) was developed for fast target delineation, which can potentially improve the efficiency of the clinical workflow. Giaj−Levra et al have demonstrated that the inter-observer difference can be reduced by using ESS (18) by evaluating the GTV contours. The aim of this study is to evaluate the accuracy of the CTV autosegmentation based on existing GTV contours using ESS for spine SBRT patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giaj-Levra et al. evaluated in a recent study the advantage of the new automatic target contouring tool (Elements Spine SRS, Brainlab ® ) for the definition of GTV ( 16 ). Using data of 20 patients with spinal metastases outlined by three independent observers, they showed that the agreement of GTV contours outlined by independent observers was superior with the use of the automatic tool compared to manually outlined contours (mean Dice coefficient 0.75 vs. 0.57, p = 0.048).…”
Section: Discussionmentioning
confidence: 99%
“…metastasis and head-neck cancer treatment planning. [25][26][27] In addition, automatic segmentation of vertebrae is facilitated by augmented reality applications and intraoperative ultrasound in intradural spinal tumour surgery in order to enhance image interpretation and thereby to support the surgeon during the surgical procedure. 28,29…”
Section: Data Evaluation/statistical Analysismentioning
confidence: 99%